SOCIAL DISCRIMINATION IN MULK RAJ ANAND, KAMALA MARKANDAYA ARUNDHATHI ROY, AND ARAVIND ADIGA NOVELS - Md. Iftakhar (International Journal of Multidisciplinary Research and Studies, 2021)
Postcolonial Indian English Fiction functions similarly to Indian English Fiction written before independence. It should always be remembered that Indian English Fiction really started to take off in the 20th century when authors like R.K. Narayan, Mulkraj Anand, and Raja Rao published their works in English. Indian English literature has received a great deal of national and international acclaim. The meticulous investigation of the English fiction written by Indian elder statesmen finds instances where their plays are not only distinctive in thought and aim but also a close imitation of the English literary template. In comparison to how Australian and American authors have developed their writing in their own countries, post-freedom Indian English anecdotal essayists have given Indian English fiction a new shape and shade. As Amar Nath Prasad observed, However, "India" as a concept has a different recorded history than its western counterpart, therefore the development of English fiction in India is closely related to the country’s postcolonial situation and imperialism’s historical background. While devoted to the perspectives of its western partners on the nonexclusive idea of fiction, Indian writing in English has struggled to reflect its social actual aspects. Thus, the current volume represents an amalgamation of the various issues and structural motifs that have characterized the growth of English-language fiction in post-freedom India.